2022
DOI: 10.3389/fpsyg.2021.788841
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and a Sense of Purpose: The Role of Personal Growth Initiative and Academic Self-Efficacy

Abstract: Objective: Studies have consistently found a positive relationship between social support and a sense of purpose; however, less is known about the underlying mechanisms of this relationship. The present study bridges this gap by proposing and testing a path model illustrating the mediating effects of personal growth initiative and academic self-efficacy on the linkage between social support and a sense of purpose.Method: A total of 2,085 Chinese college students completed the revised versions of the Social Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
1
10
0
3
Order By: Relevance
“…According to the conclusion of Zhao and Qin (2021), when students perceive more peer support, it is easier for them to carry out deep learning, and thereby students will improve their self-efficacy. In addition, previous studies have confirmed that individuals who feel more social support (from parents, peers and teachers) have a higher level of a personal growth initiative, and their self-efficacy is stronger (Cai and Lian, 2022).…”
Section: Relationships Between Variablesmentioning
confidence: 90%
See 3 more Smart Citations
“…According to the conclusion of Zhao and Qin (2021), when students perceive more peer support, it is easier for them to carry out deep learning, and thereby students will improve their self-efficacy. In addition, previous studies have confirmed that individuals who feel more social support (from parents, peers and teachers) have a higher level of a personal growth initiative, and their self-efficacy is stronger (Cai and Lian, 2022).…”
Section: Relationships Between Variablesmentioning
confidence: 90%
“…Social support refers to a material or psychological resources from individuals' social networks that help them cope with challenges (Taylor et al, 2015) and mainly includes support received from family, teachers, and peers (Wang and Eccles, 2012;Wentzel et al, 2016;Cai and Lian, 2022). According to Bronfenbrenner's (1979) bio-ecological theory of human development, proximal processes such as interpersonal relationships and social support can either promote or hinder adolescents' ability to achieve desired outcomes.…”
Section: Social Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Further on, school personnel could facilitate purpose-centered counseling and educational interventions that can help them to set academic and career goals that align with their life purpose and further discuss the value of high school education in fulfilling their life's purpose. Research has also shown that students with stronger academic self-efficacy, report greater sense of purpose ( Cai and Lian, 2021 ). With regard to academic identity, as per Bronfenbrenner's (1979) ecological systems theory and Brown et al.’s (2014) research, school personnel could foster students' academic identity through strengthening teacher-student relationships, providing challenging learning environments, and motivating students to set future educational goals and fulfill their highest potential.…”
Section: Practical Implicationsmentioning
confidence: 99%